PENGARUH CITRA PENGELOLA KUBURAN DESA TERUNYAN TERHADAP MINAT KUNJUNGAN WISATAWAN - Reni Istarini, Ni Made; Sendra, I Made; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2017)
Bali is one famous island with many potential tourism. Bangli as one of the district in Bali has begun develop it’s own potential tourism. There is a cultural village which has uniqueness called Terunyan Village Cemetery. The village cemetery has uniqueness due to the corpse is not buried or burned but placed under the tree after the death ceremony. The uniqueness this village has developed a tourist destination inducing tourist are interested in visiting Terunyan Cemetery. However the cadger and boat driver had made the tourist to be afraid to visit the Terunyan Cemetery which emerged the bad image. The research used the purposive sampling methode as a technique to determine the respondent. The number of respondents were 110 respondents. The technique of data analysis used multiple linear regression. Research in parsial show that the mirror image has a positive and significant effect toward the interesting of tourist visiting Terunyan Village Cemetery. Moreover, current image has positive and significant effect toward the tourist’s interest. In addition, wish image has positive and significant influence toward the interesting to visit. Fouthermore, corporate image has positive and significant influence to the interesting of tourist to visit. By simultaneously image has positive and significant effect toward the interesting of tourist to visit Terunyan Cemetery.
Keywords: Image, Interest, Terunyan Village Cemetery